(untitled) (International journal of artificial intelligence, 2025)
The integration of digital technologies in educational settings has fundamentally transformed pedagogical approaches, creating a paradigm shift from traditional teacher-centered methodologies to more dynamic student-centered learning environments. The analysis reveals that successful pedagogical transformation requires not merely technological implementation but strategic integration that prioritizes learner needs, promotes active participation, and fosters critical thinking skills. The research contributes to understanding how educational institutions can leverage technological innovations to create more inclusive, engaging, and effective learning environments that prepare students for the demands of the digital age.